Strategic Management and Socialpreneurship for Achieving Food Sustainability in Free Lunch Programs - Goh, Thomas Sumarsan; Suteja, Jaja; Erika, Erika; Simanjuntak, Arthur; Karsa, Aldo Hermaya Aditiya Nur; Angel, Mary (Aptisi Transactions On Technopreneurship (ATT), 2025)
Achieving Sustainable Development Goal 2 (SDG 2), which focuses on ending hunger, requires innovative approaches in strategic management and socialpreneurship food sustainability. This study investigates the intersection between these fields from 2016 to 2024. The primary objective is to analyze trends and contributions in the area of strategic management applied to food sustainability, particularly focusing on SDG 2, and to understand how business strategies and government policies can contribute to food security and hunger reduction. A bibliometric analysis was conducted using Scopus and VOSviewer to examine bibliometric relationships between countries, authors, organizations, journals, documents, and emerging keywords related to strategic management and socialpreneurship food sustainability. The study specifically looks at the growth of research and the relationship between key concepts. The analysis revealed a significant increase in research activity, with the volume of publications more than tripling from 2016 to 2023. Key countries contributing to this growth include India, Spain, and Bangladesh, with Dar es Salaam University emerging as a leader in food sustainability research in Africa. VOSviewer highlighted the rising importance of Artificial Intelligence and blockchain technologies in optimizing food security through supply chain management. The findings underscore the critical role of government policies and corporate responsibility in achieving SDG 2 and reducing hunger. Successful implementation of sustainable practices in corporate strategies requires strong collaboration between companies, government agencies, and other stakeholders.